Cultural and Entertainment Events: Enhancing Attractiveness and Promotion in a Post-Socialist City – The Kielce Case Study (Poland) - Waldemar CUDNY; Marcin WIATROWSKI (Communications of International Proceedings, 2023)
This scientific article delves into the impact of cultural and entertainment events on the tourist attractiveness and promotion of a post-socialist city of Kielce. The primary research methodology employed involved conducting a questionnaire survey among attendees of seven significant cultural and entertainment events that took place in 2019 at the Amfiteatr Kadzielnia, one of Kielce's foremost cultural venues. A total of 441 completed questionnaires were analyzed, providing insights into the perceptions and experiences of participants. The findings shed light on the effectiveness of these events in enhancing Kielce's tourist attractiveness and promotion efforts, highlighting their role in shaping the city's image as an interesting tourist destination.
Keywords: Events; post-socialist cities; tourist attractiveness; Kielce; Poland